Smoking Habits and Alcohol Use. Epidemiological data and countermeasures - Anastasia Nanou; Saridi Maria; Souliotis Kyriakos (Ene, 2015)
Alcohol consumption and smoking among adolescents worldwide is increasing without any apparent differences between developed and developing countries. Increased rates of smoking and alcohol abuse have been documented among university students worldwide. In Greece, smoking habits and alcohol consumption among university students have only been a part of wider epidemiological surveys regarding general health issues. The prevalence of smoking and alcohol consumption among university students in Greece is presumably high, but so far there haven't been any targeted efforts to focus on and deal with this issue, as it happens in other countries. Some basic factors that contribute to higher tobacco and alcohol consumption are that those products are readily available, alcoholic beverages are promoted and distributed without any formal restrictions , and smoking ban laws are for the most part neglected. The international scientific community has recently focused on the issue of tobacco and alcohol abuse among young university students and the impact on their health and the health of their social circle. Health policies addressing this issue should include prevention and intervention measures and also treatment strategies aiming both individually and at the entire university student population. The aim of this review is to inform the scientific community about the prevalence of smoking and alcohol use in university students, about factors determining this behavior and measures and policies that apply to control this phenomenon.